Health-related quality of life after burn injury due to bioethanol-fueled fireplaces - Tapking, Christian; Willkomm, L.; Stolle, A.; Harhaus-Wähner, Leila; Hundeshagen, Gabriel; Bliesener, Björn; Kneser, Ulrich; Radu, Christian Andreas (Burns, 2024)
Objective - Commercially available bioethanol-fueled fireplaces are a potential source of burns and are commonly used for home use. The present study aimed to evaluate the quality of life following burn injuries that were caused by bioethanol-related accidents. - Methods - Burned patients who were admitted to our burn unit with burn injury due to bio-ethanol fueled fire places between January 2010 and December 2021 were contacted to ask for their willingness to participate in this study. They were asked to answer questions regarding the circumstances of the accident and three questionnaires to capture burn specific and general health related quality of life (Burn Specific Health Scale-Brief (BSHS-B), Short-Form Health Survey 36 (SF-36)) and general information about the accident. Patients were matched and compared to a group of patients suffering comparable burns from other burn mechanisms, which were also admitted to our burn unit at the same time. - Results - Of 35 patients that met the inclusion criteria, 19 answered the questionnaire and were compared to 38 patients with other burn mechanisms. There were no statistical differences regarding age (bioethanol: 37.4 ± 14.7 years vs. control: 36.2 ± 14.3 years, p = 0.777), TBSA (9.9 ± 6.8% vs. 8.9 ± 10.4, p = 0.715), and sex (42.1% females vs. 36.8% females, p = 0.882). Most patients in the bioethanol-group reported that they did not follow the manual instructions (68.4%) and that the accident happened during the refilling process (52.6%). There was no significant difference in any subscale of the BSHS-B or the SF-36. - Discussion - Burns related to bioethanol-fueled fireplaces are rare compared to other typical burn mechanisms. However, as they are used for personal pleasure and interior design, psychological impairment following burn may be even more critical. Detailed education on the use of these fireplaces needs to take place in order to reduce the risk of accidents.
Online verfügbar 20 November 2023, Version des Artikels 4 April 2024
Gesehen am 02.12.2024